Comparative investigation of nanoparticles effect for enhanced oil recovery - experimental and mechanistic study. Issue 1 (1st February 2022) - Li, Yuan; Zhou, Fujian; Xu, Hang; Yu, Guolin; Yao, Erdong; Zhang, Liang; Li, Bojun
Abstract: Nanofluid flooding has become one of the advantageous enhanced oil recovery (EOR) techniques due to the transcendental property of nanoparticle. Nanoparticles with various morphology presents different effects and mechanisms of EOR. To provide some guidance on the selection of nanomaterials for flooding, 4 kinds of nanomaterials, including silicon dioxide (SiO2 ), magnesium oxide (MgO), graphene oxide (GO) and molybdenum disulfide (MoS2 ), are chosen to serve as research objects in the study. In lab, the morphology of four nanomaterials were systematically characterized by scanning electron microscope (SEM) tests. Moreover, nanofluid flooding experiments were further conducted to explore the relationship between the morphology of nanomaterials and EOR. Results show that the SiO2 was spherical structure, and the MgO was blocky structure, while the GO and MoS2 were both sheet structure. All the four nanomaterials have similar spatial dimensions. Flooding experiments revealed that MoS2 enable improves the oil recovery by approximately 11.53 %, and GO was followed with 10 %, twice as much as both SiO2 and MgO. From the results, it can be inferred that spherical materials only realize "point-to-surface" contact at multiphase interfaces, while sheet materials can achieve "surface-to-surface" contact with a higher interfacial activity. This paper is the first to focus morphology of nanomaterials on flooding, which contributes to the optimization of nanomaterials for high-efficiency oil displacement.